2016
DOI: 10.1007/s10557-016-6661-6
|View full text |Cite
|
Sign up to set email alerts
|

Remote Postconditioning Induced by Trauma Protects the Mouse Heart against Ischemia Reperfusion Injury. Involvement of the Neural Pathway and Molecular Mechanisms

Abstract: RPostCT significantly decreased myocardial infarction size via neurogenic transmission and various signaling pathways. This study describes a new cardiac I/R injury prevention method that might lead to the development of therapies that are more clinically relevant for myocardial I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…More specifically, the models have been limited to young, male mice. There has been no evidence offered that RIC is effective in aged rodents and only some evidence of its effectiveness is seen in females ( 49 , 59 , 78 ). Actually, in clinical studies, RIC would be used to treat aged persons and persons with comorbidities, such as hypertension, diabetes, and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the models have been limited to young, male mice. There has been no evidence offered that RIC is effective in aged rodents and only some evidence of its effectiveness is seen in females ( 49 , 59 , 78 ). Actually, in clinical studies, RIC would be used to treat aged persons and persons with comorbidities, such as hypertension, diabetes, and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concept of RPC confirmed that D r a f t interorgan communication may afford protection against I/R not only in the heart but also in the spinal cord, brain, liver, intestine or kidney (Haapanen et al 2016;Hausenloy and Yellon 2008). Moreover, RPC has been shown to be evoked by numerous other stimuli, such as surgical trauma (Song et al 2016), peripheral nerve stimulation (Reddington et al 2012) or by local release of autacoids (Schulz et al 1998 as depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 83%
“…The triggering stimulus can originate not only from local I/R, but also from peripheral nociception associated with surgical incision (Jones et al 2009), local surgical trauma (Song et al 2016), local activation of sensory fibers by capsaicin or electrical nerve stimulation (Redington et al 2012).…”
Section: Triggering Mechanisms and Pathways From Remote Organ To Targmentioning
confidence: 99%
“…However, it has been demonstrated that beta-blockers reduce infarct size in STEMI patients undergoing PCI [ 61 ], and this group of drugs is currently included in the guidelines for the management of these patients [ 60 ]. It has been shown that beta-adrenoreceptors are involved in the mechanisms of myocardial infarct-limiting effect of remote pre- and postconditioning of trauma [ 128 , 129 ]. The existence of some common, inherent mechanisms, such as the activation of C sensory fibers and the K(ATP) channels for both remote preconditioning of trauma [ 65 ] and RIPre/RIPer [ 5 , 83 , 117 ], may be an argument to suggest that sympathetic beta-adrenergic activation is involved in the mechanisms of RIC cardioprotection.…”
Section: Unresolved Questions and Discrepancies On The Mechanisms Of mentioning
confidence: 99%